PKCα Phosphorylates FACI to Switch Its Function in Clathrin-mediated Endocytosis to a Presumed Role in Macropinocytosis in Intestinal and Hepatic CellsSummary - Yun Cheng; Xiao-Zhuo Kang; Sin-Yee Fung; Kam-Leung Siu; Dong-Yan Jin (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: We previously identified a fasting- and CREB-H-induced (FACI) protein and defined its adaptor function in clathrin-mediated endocytosis. Both CREB-H and FACI are specifically expressed in the liver and intestine. Here, we investigated the role of FACI in macropinocytosis and its activation by protein kinase Cα. Methods: We employed a combination of biochemical, proteomic, cell biological, and microbiological assays to investigate the function of FACI in cultured cells and FACI-/- mice. Results: Phosphorylation of FACI at S9 and S37 by protein kinase Cα induces its detachment from clathrin-coated pits and relocation to the plasma membrane. FACI promotes phorbol ester-induced macropinocytosis in intestinal and hepatic cells. Interactome analysis reveals that FACI interacts with several actin remodeling proteins. FACI interacts with 14-3-3ζ to release SSH1 phosphatase from sequestration. Free SSH1 activates cofilin-1, which in turn enhances actin remodeling and macropinocytosis. Intestinal pathogens such as Salmonella typhimurium exploit FACI to facilitate their entry into host cells through macropinocytosis. Conclusion: FACI modulates clathrin-mediated endocytosis and macropinocytosis in intestinal and hepatic cells. Protein kinase Cα phosphorylates FACI to switch its function in endocytosis to a presumed role in macropinocytosis in these cells. FACI facilitates enteric pathogen invasion by enhancing macropinocytosis in the intestine.